Mesoporous CuO/MgO synthesized by a homogeneous-hydrothermal method and its catalytic performance for the ethynylation reaction of formaldehyde. Issue 19 (2nd October 2018) - Liu, Saifeng; Peng, Wencai; Zhang, Jianshu; Tong, Yanbin; Yuan, Jun; Qi, Xiaoxia; Yan, Xirui; Sun, Dekui; Dai, Bin
ABSTRACT: Mesoporous CuO/MgO catalyst was synthesized by hydrothermal homogeneous precipitation using urea as precipitating reagent. The CuO/MgO catalyst was characterized by BET-N2, X-ray diffraction pattern (XRD), scanning electron microscopy (SEM), transition electron microscopy (TEM), Raman spectra and thermogravimetric analysis (TG). The results indicate that CuO/MgO catalyst possesses extremely fine dispersion of Cu nanoparticles (NPs) with a high specific surface area of 232 m 2 /g and pore sizes of 6.5 nm. The mesoporous CuO/MgO exhibits excellent catalytic activity for the formaldehyde reaction of acetylene.